Tissue communication in a systemic immune response of Drosophila - Yang, Hairu (Fly (Austin), 2016)
Several signaling pathways, including the JAK/STAT and Toll pathways, are known to activate blood cells (hemocytes) in Drosophila melanogaster larvae. They are believed to regulate the immune response against infections by parasitoid wasps, such as Leptopilina boulardi, but how these pathways control the hemocytes is not well understood. Here, we discuss the recent discovery that both muscles and fat body take an active part in this response. Parasitoid wasp infection induces Upd2 and Upd3 secretion from hemocytes, leading to JAK/STAT activation mainly in hemocytes and in skeletal muscles. JAK/STAT activation in muscles, but not in hemocytes, is required for an efficient encapsulation of wasp eggs. This suggests that Upd2 and Upd3 are important cytokines, coordinating different tissues for the cellular immune response in Drosophila. In the fat body, Toll signaling initiates a systemic response in which hemocytes are mobilized and activated hemocytes (lamellocytes) are generated. However, the contribution of Toll signaling to the defense against wasps is limited, probably because the wasps inject inhibitors that prevent the activation of the Toll pathway. In conclusion, parasite infection induces a systemic response in Drosophila larvae involving major organ systems and probably the physiology of the entire organism.